Bank Scale of Economies, Banking Industry Concentration, and Competition Level: The Indonesian Case - BUDDI WIBOWO (Jurnal Bisnis Manajemen, 2016)
Banking sector efficiency in a country is directly influenced by regulations that set up by the banking authorities in that country, especially what kind of banking industry structure that regulator intend by those regulation. Indonesian Banking Architecture which encourage mergers and acquisitions of smaller banks, has a clear target that Indonesian banking industry should have a leaner industry structure with fewer number of banks but with relatively large assets,higher industry concentration higher and more tighter competition. This policy is driven by the regulator’s belief that Indonesian banks has not achieved its economies of scales and competition is relatively low so that the Indonesian banking operating costs are among the highest among Asian countries. The opposite actually happened in the USA where the regulator is precisely to prevent mergers between major banks due to economies of scale bank in the United States has been exceeded. The reserach results showed the group of large banks in Indonesia is more efficient than medium and small banks and the efficiency is more due to economies of scale than caused by the concentration of the industry and the level of competition between banks.